New Configuration of Handset MIMO Antenna for LTE 700 Band Applications - Byeonggwi Mun; Frances J. Harackiewicz; Byeongkwan Kim; Hyunho Wi; Jonghyun Lee; Myun-Joo Park; Changwon Jung; Byungje Lee (International Journal of Antennas and Propagation)
A compact handset multiple-input multiple-output (MIMO) antenna for long-term evolution (LTE) 700 band (746~787 MHz) applications is proposed. The proposed antenna consists of two symmetrical PIFAs. Without the usage of any additional coupling elements between closely mounted antennas, a high isolation (>15 dB) and a low enveloped correlation coefficient (ECC<0.35) are achieved by the optimum location and arrangement of MIMO antenna elements.